Experimental study of oil film thickness on workpiece under minimum quantity lubrication milling process using laser induced fluorescence method - Nur Izzati Khoirunnisa, Ismail (2022)
In machining process, lubricant is utilized in order to facilitate higher production for lubrication and cooling purpose to reduce cutting force, cutting temperature and friction near the cutting zone. Conventional flooding technique is the most universal medium used by the manufacturer however, the used of large amount of lubricant contributes to high manufacturing cost and jeopardizing workers health. Thus, continuous effort of researchers to substitute the flood cooling has found a better approach that is minimum quantity lubrication (MQL) technology. MQL promotes diverse benefits to the manufacturers, in terms of manufacturing cost and employees’ health’s. Superior advantage in using MQL is attributed by its compelling performance that promotes sufficient lubrication along the cutting edge with small amount of oil. However, the lubricant oil must be ensured to well penetrate the cutting zone. In order to explain this situation, the lubricant oil mist sprayed onto workpiece upon the on-going operation must be analysed in depth. This can be accomplished by observing the amount of oil mist adhered near the cutting edge. However, past researchers concern merely on the machining parameters effects towards the performance of MQL. The studies on the behavior of lubricant oil during MQL machining operation is limited since it is a challenging task to observe the lubricant oil during MQL machining is on-going. Moreover, the preferable size of droplet obtained at short nozzle distance and medium air pressure can efficiently wet the cutting surface. Furthermore, MQL lubricant oil flow rate is among the factor to enable the adjustment of pressure between lubricant oil in the tank of MQL generator and atmospheric pressure to make sure oil mist generated is sufficient for the lubrication effect. Therefore, the objectives of this study are set to measure lubricant oil film thickness at cutting zone, to examine surface roughness of workpiece under different MQL nozzle positons and lubricant oil flow rates using laser induced fluorescence (LIF) method during MQL milling process and to identify relationship between lubricant oil film thickness and surface roughness. Lubricant oil film thickness was evaluated by applying equation from the calibration procedure for the LIF method. As a result, it was found that; the range of lubricant oil film thickness increased with increasing oil flow rates for both MQL nozzle positions of 0° and 45°. Suggested that at MQL nozzle position of 0°, more lubricant oil film thickness reached higher ranges which were shown by more negative skewness distribution of histogram as well as nearly symmetrical histogram compared to nozzle position of 45°. Then, for average surface roughness it was found that; at 0° MQL nozzle position, all mean roughness values decreased with increasing oil flow rates. This could be due to the gain in oil film thickness at high range which is 0.5 mm until 0.9 mm and above. However, at nozzle position of 45°, for higher lubricant oil flow rates, the values of mean surface roughness were higher compared to mean surface roughness of MQL nozzle position of 0°. This could be associated with lower lubricant oil film thickness gained in the range of 0.3 mm until 0.7 mm. Therefore, it is proven that at 0° MQL nozzle position, increasing MQL flow rate; makes lubricant oil more capable to be effectively delivered into the cutting zone of workpiece. Here, relationship between lubricant oil film thickness and surface roughness was successfully identified in this study. These findings potentially benefit for MQL milling process of hard material such as aluminium alloy 6061.